Strategi Stimulasi Kognitif Berbasis Bermain untuk Anak Usia Dini - Sari, Wulan Purnama; Auliya, Puri; Wahyuni, Sri (JOECE: Journal of Early Childhood Education, 2025)
Early childhood, especially in the age range of 0 to 8 years, is a crucial stage in the process of human growth and development because in this period there is an acceleration of brain development. One of the important factors that influence this stage is cognitive stimulation, which includes the ability to think, recognize patterns, solve problems, and understand cause-and-effect relationships. Play is an effective way to encourage children's cognitive growth, because through this fun activity, children can explore ideas, hone their imagination, and learn to solve various challenges. Play also supports memory, focus, and social skills such as cooperation, sharing and conflict resolution. Thus, play-based approaches are essential in supporting the holistic development of early childhood. This study aims to explore play strategies that can effectively stimulate children's cognitive development, as well as provide applicative guidance for parents and educators to optimize these methods. It is hoped that the findings from this research can be a source of insight for creating play activities that are not only fun but also full of educational value, in order to support the maximum learning experience for children.